Takhrij and Syarah Hadith of Chemistry: Cashew Fruit Fermentation can Produce Alcohol - Mustika Tri Anggraeni; Afianda Ghinaya Aulia; Vina Amalia; Ahmad Gibson Al Bustomi; Gustiana Isya Marjani (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet SAW. about the relationship between khamr and alcohol in cashew fruit fermentation. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study were the fermentation of cashew nuts reaching a level of 14.98% which has an intoxicating potential such as khamr. The conclusion of this research is takhrij and syarah hadith of the Prophet SAW. about the comparison of khamr and alcohol in fermented beverages from the perspective of the hadith with chemical analysis.